THE PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN YANG DIMEDIASI OLEH KEPUASAN PELANGGAN RICHEESE FACTORY DI KOTA BANDUNG: PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN YANG DIMEDIASI OLEH KEPUASAN PELANGGAN RICHEESE FACTORY DI KOTA BANDUNG - Candy, Albertus; Adialita, Tania (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
This research aims to analyze the influence of service quality on customer loyalty which is mediated by Richcheese Factory customer satisfaction in Bandung City. Researchers used convenience sampling techniques which are part of non-probability sampling. The specified sample consisted of 120 respondents. The data that researchers obtained through primary data in the form of survey results and secondary data from Topbrandaward in 2023. The data was analyzed through validity tests, reliability tests, classical assumption tests, simple regression tests, multiple regression tests, hypothesis tests, and Sobel tests. The results of this research are as follows: 1) Service quality has a positive and significant effect on Richeese Factory customer satisfaction in Bandung City, 2) Service quality has a positive and significant effect on Richeese Factory customer loyalty in Bandung City, 3) Customer satisfaction has a positive effect on customer loyalty Richeese Factory in Bandung City. 4) Customer satisfaction plays a positive role in mediating the influence of service quality on customer loyalty at the Rich Cheese Factory in Bandung City.